1982
DOI: 10.1139/m82-156
|View full text |Cite
|
Sign up to set email alerts
|

Wine yeast isozymes. I. Genetic differences in 18 stock cultures

Abstract: Electrophoretic analysis of three dehydrogenase and two reductase isozymes was performed on 18 commonly used yeast strains. Gene polymorphism was noted for all five isozyme activities. Based on the homology of banding patterns, two main groups of yeast strains were identified. No two yeast strains had identical banding patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Our results differ from those obtained by other authors in studies on the electrophoretic mobility of isoenzymes in the species examined of the genus Saccharomyces as they generally present a greater intraspecific diversity in patterns and fail to separate the four species belonging to Succhuromyces senm stricto (Subden et al, 1982;Yamazaki et al, 1983;Poncet et al, 1992;Lewicka et al, 1995). The experimental conditions, namely the use of certified strains and the time of harvesting the cells, may account for the consistency of these results.…”
Section: Numerical Analysis Of Isoenzyme Profilescontrasting
confidence: 94%
See 1 more Smart Citation
“…Our results differ from those obtained by other authors in studies on the electrophoretic mobility of isoenzymes in the species examined of the genus Saccharomyces as they generally present a greater intraspecific diversity in patterns and fail to separate the four species belonging to Succhuromyces senm stricto (Subden et al, 1982;Yamazaki et al, 1983;Poncet et al, 1992;Lewicka et al, 1995). The experimental conditions, namely the use of certified strains and the time of harvesting the cells, may account for the consistency of these results.…”
Section: Numerical Analysis Of Isoenzyme Profilescontrasting
confidence: 94%
“…1). In similar studies, based on a higher number of enzymes, the authors report as many different ETs as the number of strains under study (Subden et al, 1982;Yamazaki et al, 1983;Poncet et al, 1992). In contrast, Lewicka et al (1995) in studies of genetic diversity based on multilocus starch electrophoresis of seven isoenzymes described 11 different ETs for 27 strains of S. cerevisiae, which is in accordance with our results and indicates that the discriminatory power of the enzymes varies significantly.…”
Section: Resultsmentioning
confidence: 92%
“…In contrast, other studies have shown that the cultivated yeasts S. cerevisiae, S. bayanus, and S. pastorianus are very polymorphic for many enzymes (10,32,39). For example, among 18 S. cerevisiae isolates taken from stock cultures of wine yeasts, no two yeasts had identical electrophoretic patterns for five enzymes studied (32).…”
Section: Discussionmentioning
confidence: 77%
“…Enzyme electrophoresis has been widely used in population genetic studies of bacteria and higher eucaryotes and in some fungi (8,36,37,40,41), but the method has not yet been used to study natural yeast populations to any appreciable degree. Limited studies of enzyme polymorphism in the Saccharomyces sensu stricto complex have been performed, for the most part, with the cultivated yeast S. cerevisiae (10,32,39).…”
mentioning
confidence: 99%
“…Recently the genus Saccharomyces has been investigated chemotaxonomically to elucidate the relationships of its species (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The electrophoretic patterns of its enzymes were also studied (23,24), but these studies were restricted to S. cerevisiae and were very limited taxonomically and physiologically.…”
mentioning
confidence: 99%